Answer with Explanation:
The general wave equation is given by
[tex]\frac{\partial ^2u}{\partial x^2}+\frac{\partial ^2u}{\partial y^2}=\frac{1}{c^2}\frac{\partial ^2u}{\partial t^2}[/tex]
where
'c' is the velocity of the wave
Comparing with the given equation
[tex]\frac{\partial ^2h}{\partial x^2}+\frac{\partial ^2h}{\partial y^2}=\frac{1}{gd}\frac{\partial ^2h}{\partial t^2}[/tex]
We can see that
[tex]c^2=gd\\\\\therefore c=\sqrt{gd}[/tex]
Thus the velocity of wave is given by [tex]v=\sqrt{gd}[/tex]